Tick-borne encephalitis vaccine uptake, effectiveness, and impact in Sweden from 2018 to 2022 - Andreas Palmborg; Frederick J. Angulo; Pingping Zhang; Andreas Pilz; James Stark; Jennifer C. Moïsi; Luis Jodar (Scientific Reports)
Abstract Tick-borne encephalitis (TBE) is an increasing health threat in Sweden and elsewhere in Europe. TBE vaccination is commonly recommended in Sweden, but limited data are available on uptake, effectiveness, and impact of TBE vaccination. General population surveys conducted in 2019–2022 were used to estimated TBE vaccine uptake. TBE vaccine effectiveness (VE) was estimated using the screening method utilizing the surveys and public health TBE surveillance data, which predominately includes hospitalized TBE cases, from 2018 to 2022. Impact of TBE vaccination was calculated based on disease incidence and observed VE. In 2018–2022, 2,015 TBE cases were reported in Sweden; 82.8% (1,564/1,890) of cases with known TBE vaccination history were unvaccinated. Among persons surveyed from the general population with known vaccination history, 52.0% (11,562/22,247) were unvaccinated. Three dose VE against TBE was 89.0% (95% confidence interval 84.3–92.4). When stratified by age group, VE was 86.0% (55.7–95.6) in 1–15 years-of-age and 93.8% (87.5–96.9) in 16–49 years-of-age. In a conservative estimate, despite suboptimal compliance with TBE vaccination recommendations, vaccination averted an estimated thousand TBE cases, most resulting in hospitalization, in Sweden from 2018 to  2022. To prevent additional TBE cases in Sweden, enhanced efforts to increase TBE vaccine uptake and compliance to the TBE vaccination schedule are needed.